2011 International Symposium on Intelligent Signal Processing and Communications Systems (ISPACS) 2011
DOI: 10.1109/ispacs.2011.6146067
|View full text |Cite
|
Sign up to set email alerts
|

Resistance against power analysis attacks on adiabatic dynamic and adiabatic differential logics for smart card

Abstract: Numerous articles and patents on the masking of logic gates in CMOS logic styles have been reported, however, less information is available with regards to comparing the single rail and dual-rail on masking input logic values. This paper investigates single-rail and dual-rail logic families that have been developed by the logic designers for secure logic implementations in cryptographic system. The novelty of this work is that we evaluate the dynamic logic and ditTerential logic for one-phase 2-inputs logic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The proposed logic charge the same capacitance value for each input combination. Lastly, the existing logic designs have been assessed for their resistance against PAA using the inputs which do not follow the adiabatic principle [8]. Also the inputs used are the one which will not come out of an adiabatic circuit.…”
Section: Shortcomings In the Existing Secure Adiabatic Logic Designsmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed logic charge the same capacitance value for each input combination. Lastly, the existing logic designs have been assessed for their resistance against PAA using the inputs which do not follow the adiabatic principle [8]. Also the inputs used are the one which will not come out of an adiabatic circuit.…”
Section: Shortcomings In the Existing Secure Adiabatic Logic Designsmentioning
confidence: 99%
“…Fig. 2 (a) and (b) shows the 16 input transitions for 2-input gate as shown in [8] and the real life relevant adiabatic input transitions respectively. The problem with the input transitions of Fig 2(a) is that it favours the energy efficiency of the logic by removing the coupling effects and the NAL during the recovery phase of the power-clock.…”
Section: Shortcomings In the Existing Secure Adiabatic Logic Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultra low-power adiabatic sequential circuits like D, JK, T flip-flops are explored in [7]. Besides, it was reported that the adiabatic logic styles have better differential power analysis (DPA) resistances than the conventional CMOS logic [8,9]. However, with the aggressive scaling of device technology and threshold voltage, the leakage current has increased significantly, becoming the main part of power consumption [10].…”
Section: Introductionmentioning
confidence: 99%
“…Almost no research exists in the security of adiabatic logic against power analysis attacks. A short analysis on a 2-input NAND gate was described in [6], but no conclusion was made regarding adiabatic logic's security based on the experiment. Additionally, no analysis on larger gates was done.…”
Section: Introductionmentioning
confidence: 99%